PENGARUH HEDONIC MOTIVATION, PRICE VALUE DAN RISK PERCEPTION TERHADAP FINTECH ADOPTION PADA KALANGAN MAHASISWA DI KOTA BATAM - Wangdra, Jacelyn; Ompusunggu, Hermaya (SCIENTIA JOURNAL, 2025)
Nowadays, students in Batam City are increasingly using Fintech services as a financial management solution. Fintech is a service provider that supports the transaction process to be faster. Students sometimes do not realize that Fintech had changed their lifestyle to become more consumptive, did not realize that there are differences in perception of the value of the prices paid, and most recently the emergence of fear. This research aims to investigate the influence of hedonic motivation, price value and risk perception towards Fintech Adoption among students in Batam. This research used quantitative techniques. The sampling technique that was used is the Slovin Formula with a total of 167 respondents as barbarslot a means of determining the number of samples selected using purposive sampling. Data collection was carried out by distributing questionnaires via Google Form. Descriptive statistical test, validity test, reliability tests, and normality test used SPSS 26. The results of regression analysis to 1.334 Accounting students in Batam show that Hedonic Motivation (X1) and Price Value (X2) has positive and significant effect on Fintech Adoption (Y). Risk Perception (X3) on the other hand, is not as significant. The F-test shows that the regression model was significant enough overall (F = 116.228; p < 0.05), meaning the three variables collectively influenced Fintech Adoption. An R² value of 0.681 suggested that 68.1% of the variance in Fintech Adoption was explained by the model, while the remaining 31.9% was attributed to other factors outside the study.